Immigrant song: males and females learn songs after dispersal in a tropical bird. (9th April 2018) - Graham, Brendan A; Heath, Daniel D; Walter, Ryan P; Mennill, Daniel J
Abstract : Does immigration influence acoustic variation in male and female tropical songbirds? The influence of immigration has been studied in males, but not previously in females. We identified first-generation migrants in 3 populations of Rufous-and-white Wrens in Costa Rica. We found that songs of both sexes of first-generation migrants match the songs of their breeding population. We conclude that song learning in first-generation migrants must be influenced by birds in their breeding population, following postnatal dispersal. Abstract: A fundamental hypothesis about vocal learning is that young animals learn vocalizations in their natal areas and, following postnatal dispersal, they may introduce new types of vocalizations into their breeding areas. We tested this hypothesis in a tropical bird, the Rufous-and-white Wren ( Thryophilus rufalbus ), a species in which both sexes produce learned songs. We collected blood samples and acoustic recordings from 146 adult wrens from 3 populations in northwestern Costa Rica. We genotyped individuals at 10 polymorphic microsatellite loci and identified first-generation migrants using partial Bayesian genotype assignment. We quantified acoustic variation by comparing fine-scale acoustic structure, song sharing, and repertoire novelty between residents and first-generation migrants. We found significant population-level differences in acoustic structure of songs among the 3 populations. Of the 146 individuals genotyped, 9 individuals were identified as first-generation migrants. In contrast to our predictions, however, we found that these first-generation migrants did not exhibit differences in the acoustic structure of their songs from resident individuals in their breeding population, either for males or females. We conclude that song learning in first-generation migrants must be behaviorally influenced by birds in their breeding populations, following postnatal dispersal. We observed population-level acoustic differences among the 3 study sites, which implies sustained divergent selection pressures at each site, possibly reflecting acoustic adaptation to different environments or social pressure to sing local songs. Understanding and quantifying patterns of cultural evolution at multiple scales provides insight into how behavioral barriers, such as acoustic signals, contribute to population differentiation and even speciation.